1997
DOI: 10.1161/01.atv.17.11.2554
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Fasting Total Plasma Homocysteine Levels and Cardiovascular Disease Outcomes in Maintenance Dialysis Patients

Abstract: There is an excess prevalence of hyperhomocysteinemia in dialysis-dependent end-stage renal disease (ESRD) patients. Cross-sectional studies of the relationship between elevated total homocysteine (tHcy) levels and prevalent cardiovascular disease (CVD) in this patient population suffer from severe methodologic limitations. No prospective investigations examining the association between tHcy levels and the subsequent development of arteriosclerotic CVD outcomes among maintenance dialysis patients have been rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
132
2
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(144 citation statements)
references
References 26 publications
7
132
2
3
Order By: Relevance
“…Association between tHcy and hospitalization frequency, i.e., total number of hospital admissions, over the 12-month follow-up period, as reflected by hospitalization rate ratios (RR) and 95% confidence intervals a Moreover, in the aforementioned study, neither serum albumin nor CRP predicted mortality, whereas our study did. Hence, the reason that our current study and three other recent studies (10 -12) found the opposite association as compared with a few others (7,9,42) could be due to differences in race or ethnicity, comorbidities, the prevalence of diabetes, and/or study designs. Moreover, publication bias may have handicapped or delayed reporting such paradoxical findings in dialysis patients, because the investigators' first impression upon encountering results with inverse association between tHcy and mortality may be to consider them erroneous or flawed and hence to avoid reporting them (15,43,44).…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Association between tHcy and hospitalization frequency, i.e., total number of hospital admissions, over the 12-month follow-up period, as reflected by hospitalization rate ratios (RR) and 95% confidence intervals a Moreover, in the aforementioned study, neither serum albumin nor CRP predicted mortality, whereas our study did. Hence, the reason that our current study and three other recent studies (10 -12) found the opposite association as compared with a few others (7,9,42) could be due to differences in race or ethnicity, comorbidities, the prevalence of diabetes, and/or study designs. Moreover, publication bias may have handicapped or delayed reporting such paradoxical findings in dialysis patients, because the investigators' first impression upon encountering results with inverse association between tHcy and mortality may be to consider them erroneous or flawed and hence to avoid reporting them (15,43,44).…”
Section: Discussioncontrasting
confidence: 87%
“…This possibly flawed reasoning is known in epidemiology as ecological fallacy, in that inferences are based on comparing populations rather than individuals (41). However, a few stud- ies indeed have shown a positive correlation between tHcy and poor outcome (7,9,42), but they are subject to restrictions. For instance, in the study by Mallamaci et al (7), although tHcy was found to be positively associated with cardiovascular outcome in 175 MHD patients who were followed for an average of 29 mo, it failed to independently predict survival.…”
Section: Discussionmentioning
confidence: 99%
“…In ESRD, mean total homocysteine levels (tHcy) are commonly elevated, and the role of homocysteine as risk factor has been suggested in some small prospective studies (3)(4)(5). However, some studies in ESRD have observed an inverse relationship between tHcy and cardiovascular disease (6,7).…”
mentioning
confidence: 99%
“…All these abnormalities have been identified to be a sole risk factor for atherosclerosis, [12][13][14][15] with poor results with dialysis treatment. [16] An increased plasma homocysteine concentration is more among hemodialysis patients, [17,18] and also considered to be risk factor for atherosclerotic complications of ESRD. [19][20][21][22] CKD is associated with increase in triglyceride level, due to increase in VLDL, chylomicrons, and its remnants.…”
Section: Introductionmentioning
confidence: 99%